PERBANDINGAN PENGARUH PENGGUNAAN BANTUAN PETI LOMPAT DAN ORANG TERHADAP PENINGKATAN KETERAMPILAN GERAK HEADSPRING DAN HANDSPRING DALAM LATIHAN SENAM ARTISTIK DITINJAU DARI FLEKSIBILITAS TOGOK - YUDI KARISMA SARI (Universitas Tunas Pembangunan, 2015)
COMPARASION OF THE INFLUENCE OF THE USE AND THE JUMP TI INCREASED SKILL MOTION HEADSPRING AND HANDSPRING IN GYMNASTICS ARTTISTIC EXERCISE IN TERMS OF FLEXIBILITY TOGOK (Experimental Study On The Students Sports Son Coaching Education Faculty Oof Teacher Trainning And Educatuional Sciences Of TheÂ Tunas Pembangunan University Of Surakarta). Headspring and handspring is one type of movement on the number of floors (floor exercise) that have an element of movement is difficult and complex. That students have the ability and handspring owned headspring students well and properly, it must be done in a systematic and continuous training in the necessary training and exercise strategies. Use of aid is an important part in the implementation of skills training to improve skills including headspring and handspring. The use of such assistance in the implementation of the exercise as a media form that is appropriate use of assistance, including the use of aid in the form of tools (box jump) or use the help of people. On exercise and handspring headspring should be given proper training on the use of aid in a variety of exercises that can be useful to improve the motion headspring and handspring for students. The aims of the research to determine: (1a) The difference of effect between the use of jump box and person aids on the improvement of headspring movement in artistic gymnastic, (1b) The difference of headspring movement improvement result in artistic gymnastic practice between the students with high, medium, and low torso flexibility, (1c) The effect of interaction between the use of jump box and person aids, and the torso flexibility on the improvement of headspring movement in artistic gymnastic, (2a) The difference of effect between the use of jump box and person aids on the improvement of handspring movement in artistic gymnastic, (2b) The difference of handspring movement improvement result in artistic gymnastic practice between the students with high, medium, and low torso flexibility, (2c) The effect of interaction between the use of jump box and person aids, and the torso flexibility on the improvement of handspring movement in artistic gymnastic, (3a) The difference of effect between the use of jump box and person aids on the improvement of headspring-handspring movement in artistic gymnastic, (3b) The difference of headspring-handspring movement improvement result in artistic gymnastic practice between the students with high, medium, and low torso flexibility, (3c) The effect of interaction between the use of jump box and person aids, and the torso flexibility on the improvement of headspring-handspring movement in artistic gymnastic practice. This research used an experimental method with a 2 x 3 factorial design. The population of research was the third semester male students of Sport and Health Education Department of Teacher Training and Education Faculty of Surakarta Tunas Pembangunan University (UTP) who had attended Gymnastics I and II courses. The sampling technique used was purposive random sampling. The sample size was 36 students. Techniques of collecting data used were test and measurement. The data was collected included headspring, handspring, and headspring-handspring sequence movement scores with gymnastic referee assessment. The data of torso flexibility was collected using Bridge Step Test. Technique of analyzing data used in this research was variance analysis and Newman Keuls interval test at significance level of 5%. Based on the result of research conducted, the following conclusions could be drawn: (1a) there was a different effect between the use of jump box and person aids on the improvement of headspring movement in artistic gymnastic, Fstatistic = 11.15 > Ftable = 4.26. (1b) There was a difference of headspring movement improvement result in artistic gymnastic practice between the students with high, medium, and low torso flexibility, Fstatistic = 8.18 > Ftable = 3.40. (1c) There was no interaction between the use of jump box and person aids, and the torso flexibility on the improvement of headspring movement in artistic gymnastic, Fstatistic = 3.295 > Ftable = 3.40. (2a) there was a different effect between the use of jump box and person aids on the improvement of handspring movement in artistic gymnastic, Fstatistic = 9.295 > Ftable = 4.26. (2b) There was a difference of handspring movement improvement result in artistic gymnastic practice between the students with high, medium, and low torso flexibility, Fstatistic = 7.325 > Ftable = 3.40. (2c) There was no interaction between the use of jump box and person aids, and the torso flexibility on the improvement of handspring movement in artistic gymnastic, Fstatistic = 2.965 > Ftable = 3.40. (3a) There was a difference of effect between the use of jump box and person aids on the improvement of headspring-handspring movement in artistic gymnastic practice, Fstatistic = 13.375 > Ftable = 4.26. (3b) There was a difference of headspring-handspring movement improvement results in artistic gymnastic practice between the students with high, medium and low torso flexibility, Fstatistic = 11.28 > Ftable = 3.40. (3c) The was no interaction effect between the use of jump box and person aids uses and the torso flexibility on the improvement of headspring-handspring movement in artistic gymnastic practice, Fstatistic = 3.326 > Ftable = 3.40.